Antibiotic resistance potential of the healthy preterm infant gut microbiome - Rose,G; Shaw,AG; Sim,K; Wooldridge,DJ; Li,M-S; Gharbia,S; Misra,RV; Kroll,J (PeerJ, 2017)
Background: Few studies have investigated the gut microbiome of infants, fewer still preterm infants. In this study we sought to quantify and interrogate the resistome within a cohort of premature infants using shotgun metagenomic sequencing. We describe the gut microbiomes from preterm but healthy infants, characterising the taxonomic diversity identified and frequency of antibiotic resistance genes detected.Results: Dominant clinically important species identified within the microbiomes included C. perfringens, K. pneumoniae and members of the Staphylococci and Enterobacter genera. Screening at the gene level we identified an average 13 genes per preterm infant, ranging across 8 different antibiotic classes, including aminoglycosides and fluoroquinolones. Some antibiotic resistance genes were associated with clinically relevant bacteria, including the identification of mecA and high levels of Staphylococci within some infants. We were able to demonstrate that in a third of the infants the S. aureus identified was unrelated using MLST or metagenome assembly, but low abundance prevented such analysis within the remaining samples.Conclusions: We found that the healthy preterm infant gut microbiomes in this study harboured a significant diversity of antibiotic resistance genes. This broad picture of resistances and the wider taxonomic diversity identified raises further caution to the use of antibiotics without consideration of the resident microbial communities.